Development and Characterization of Calendula officinalis Extract-Loaded Topical Gels For Use In Inflammatory Skin Conditions Associated With Staphylococcus aureus and Pseudomonas aeruginosa in Diabetic Foot Ulcers - Kaur, Ramandeep; Rathore, Charul; Barik, Bhakti Bhusan; Samanta, Anuva; Rahamanulla, Abdul; Jafar, Mohammed; Mohammed, Jaffer Sadik; Krishna, Konda V V S (Journal of Neonatal Surgery, 2025)
In order to treat bacterial skin infections linked to diabetic foot ulcers, the current study focusses on the creation and assessment of a topical herbal gel formulation including microwave-assisted Calendula officinalis leaf extract (COLE-MA). Opportunistic organisms like Pseudomonas aeruginosa and Staphylococcus aureus frequently infect diabetic wounds, causing serious consequences and delayed recovery. Six gel formulations (HGF1–HGF6) were prepared using Carbopol 934, with HGF4 emerging as the optimal formulation based on ideal pH, viscosity, spreadability, and extrudability. According to zero-order kinetics (R2 = 0.9860), in vitro diffusion experiments demonstrated a sustained release profile for HGF4, reaching 99.98% release in 5 hours. Lipid peroxidation was significantly inhibited by antioxidant activity measured by the TBARS assay. With MIC values of 0.16 mg/mL against S. aureus and 0.12 mg/mL against P. aeruginosa, HGF4 also demonstrated significant antibacterial activity. Its capacity to prevent the growth of important wound pathogens suggests therapeutic potential, even if its bactericidal activity was less than that of conventional antibiotics. These findings suggest that the COLE-MA herbal gel could serve as an effective topical treatment for infected diabetic foot ulcers, combining natural antioxidant and antibacterial actions with a safe and skin-compatible formulation